Study of control and utilization rights of forestry results in Indonesia viewed from legal aspect - R. Budi Prawoto (Fakulti Undang - Undang, 2003)

(untitled)
In the era of global economy, it appears that some demands for business to give more attention to the forest environments issues as a natural and economic resource of development. Forest is a property of Indonesia, in which its utilization and control must consider the environmental aspects and society welfare. The purpose of this research is to know the extent of forest management in Indonesia with all aspects of its legal protection, so that the control and utilization of the forest results can be done property. The result of the research review shows that all regulations for saving Indonesian forests are not fully obeyed and the law enforcements in forest field are still beyond what is expected